Epidemiological & clinical profile of influenza A (H1N1) 2009 virus infections during 2015 epidemic in Rajasthan - Bharti Malhotra (Indian Journal of Medical Research, 2016)
Background & objectives: Pandemic influenza A (H1N1) 2009 virus emerged in 2009 and caused pandemic with high morbidity and mortality in India and worldwide. The number of H1N1-positive cases varied in different years in Rajasthan. The objective of the study was to present the epidemiological profile of pandemic influenza A (H1N1) 2009 virus cases in Rajasthan from January to March 2015. Methods: A retrospective descriptive, record-based analysis of suspected and confirmed cases of pandemic influenza A (H1N1) 2009 virus infection in Rajasthan, India, from January to March 2015 was performed. Testing was done as per the Centers for Disease Control guidelines at nine laboratories approved by the Government of Rajasthan. Data were analyzed in terms of demographic characteristics, clinical presentation and outcome. Results: Among 18,187 tested cases, 6203 (34.10%) were positive. Death occurred in 378 cases, with six per cent case fatality rate. Maximum number of cases (n=2801) and deaths (n=101) were from Jaipur zone. The highest number of cases, 47.60 per cent (2953/6203) and deaths, 52.11 per cent (197/378) were in the age group of 26-50 yr; 52.64 per cent (199/378) of deaths occurred in females. The highest number (63.5%) of deaths was from urban areas. Associated risk factors were observed in 59.44 per cent of the death cases, pregnancy being the predominant predisposing factor. In 61.92 per cent of patients, death occurred within three days of hospitalization. Interpretation & conclusions: H1N1 epidemic caused high morbidity and mortality in early 2015, particularly in the younger and middle-aged population and pregnant women in Rajasthan State of India. The study highlights the regular surveillance of influenza like illness, early diagnosis and timely initiation of therapy in suspected cases.